Analisis Nilai Tambah dan Keuntungan Pengolahan Daun Serai Wangi di Desa Pinilih Kecamatan Dimembe Kabupaten Minahasa Utara - Lonta, Amsye; Loho, Agnes Estephina; Pakasi, Caroline Betsi Diana (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The purpose of this study was to determine the added value and profit from processing citronella leaves into citronella oil in Pinilih Village, Dimembe District, North Minahasa Regency. The implementation of this research was carried out for 3 months starting from May to July 2023, starting from preparation to report preparation. This research was conducted in Pinilih Village, Dimembe District, North Minahasa Regency. The data used in this research are primary data and secondary data. The data collection techniques used were observation, interview and documentation. The data analysis used is using value-added analysis according to the Hayami method. Based on research in one production business processing citronella leaves into citronella oil using 500 Kg of citronella leaves which can produce 132 bottles of citronella oil. The results of the value-added analysis show that processing citronella leaves into citronella oil produces an added value of IDR 4,906 /30 ml bottle with a value-added ratio of 66.47% and a profit of IDR 4,106 /30 ml bottle with a profit level received by the business owner of 64.35%.